2019
DOI: 10.1002/aocs.12190
|View full text |Cite
|
Sign up to set email alerts
|

Role of Flaxseed Meal Feeding for Different Durations in the Lipid Deposition and Meat Quality in Broiler Chickens

Abstract: This study investigated the role of flaxseed meal (FSM), a rich terrestrial source of ω-3 fatty acids, in the alteration of the fatty acid profile and metabolism, health indices, physicochemical properties, and sensory quality of broiler chicken meat. The broiler chickens were fed 100 g FSM kg −1 diet for different time periods (1, 2, 3, 4, and 5 weeks). The results revealed that 100 g FSM feeding in broiler chickens for at least 3 weeks increased (P < 0.01) the EPA, DHA, MUFA, PUFA, ω-3 PUFA, and ω-6 PUFA of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

17
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(55 citation statements)
references
References 51 publications
17
38
0
Order By: Relevance
“…The results of sensory evaluation of broiler chicken meat are corroborated by the studies of Mridula et al [33,36] who observed that organoleptic properties of meat did not show any significant effect of FSM inclusion in the diet of broiler chicken. Further, sensory quality of breast or thigh meat [42] and sensory values (aroma, flavour, aftertaste, overall acceptability) of breast and thigh meat patties made for chicken fed did not exhibit any significant effect of [8,11,12,14,34,41]. Broiler chicken do have the ability to convert some dietary ALA to EPA, DPA, and DHA [11,12] which indicates that EPA and DHA can be made available from chicken meat conveniently other than the conventional marine sources.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The results of sensory evaluation of broiler chicken meat are corroborated by the studies of Mridula et al [33,36] who observed that organoleptic properties of meat did not show any significant effect of FSM inclusion in the diet of broiler chicken. Further, sensory quality of breast or thigh meat [42] and sensory values (aroma, flavour, aftertaste, overall acceptability) of breast and thigh meat patties made for chicken fed did not exhibit any significant effect of [8,11,12,14,34,41]. Broiler chicken do have the ability to convert some dietary ALA to EPA, DPA, and DHA [11,12] which indicates that EPA and DHA can be made available from chicken meat conveniently other than the conventional marine sources.…”
Section: Discussionmentioning
confidence: 99%
“…Further, sensory quality of breast or thigh meat [42] and sensory values (aroma, flavour, aftertaste, overall acceptability) of breast and thigh meat patties made for chicken fed did not exhibit any significant effect of [8,11,12,14,34,41]. Broiler chicken do have the ability to convert some dietary ALA to EPA, DPA, and DHA [11,12] which indicates that EPA and DHA can be made available from chicken meat conveniently other than the conventional marine sources. There are no such reports available on chicken showing the effects of Cr on fatty acid profile of chicken meat.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations